Pengaruh Kualitas SIMRS dan Lingkungan Kerja Non Fisik terhadap Kinerja Pegawai dan Person-Organization Fit (Studi Kasus pada Rumah Sakit Islam Jemursari Surabaya) - Muntari, Muntari; Djawoto, Djawoto; Suwitho, Suwitho; Oetomo, Hening Widi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Employee performance is an important aspect of overall company performance. Hospitals as a complex organization require effective and efficient employee performance in providing services to the community. This study aims to analyze the effect of SIMRS quality and non-physical work environment on person-organization fit and employee performance at RSI Jemursari Surabaya. The sample of this study was permanent employees who were SIMRS users at Jemursari Hospital as many as 85 respondents. The data collection tool uses a questionnaire with a Likert scale modification and uses the Partial Least Square (PLS) analysis method that is run with SmartPLS 3.0 software to analyze the data. The results showed that the quality of SIMRS had a positive and significant effect on person-organization fit, non-physical work environment had a positive and significant effect on person-organization fit, the quality of SIMRS had a positive effect on employee performance but not significantly, non-physical work environment had a positive influence on performance employees but not significant, and person-organization fit has a positive and significant effect on employee performance.